2009
DOI: 10.1007/978-3-642-02815-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Brønsted Acids for Asymmetric Organocatalysis

Abstract: Chiral Brønsted acid catalysis is an emerging area of organocatalysis. Since the pioneering studies of the groups of Akiyama and Terada in 2004 on the use of chiral BINOL phosphates as powerful Brønsted acid catalysts in asymmetric Mannich-type reactions, numerous catalytic asymmetric transformations involving imine activation have been realized by means of this catalyst class, including among others Friedel-Crafts, Pictet-Spengler, Strecker, cycloaddition reactions, transfer hydrogenations, and reductive amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 94 publications
0
34
0
Order By: Relevance
“…A subsequent nucleophilic addition to silicon removes the acetal directing groups and provides unmasked phenol products 9 in a single vessel. Importantly, the resulting ortho -silyl phenols 9 are useful synthetic vehicles for direct applications to many other important transformations, examples of which include harnessing aryne chemistry, 23 Au-catalyzed oxidative cross-coupling, 4d,e synthesis of dibenzosiloles, 24 and catalytic synthesis of a chiral BINOL 25 scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent nucleophilic addition to silicon removes the acetal directing groups and provides unmasked phenol products 9 in a single vessel. Importantly, the resulting ortho -silyl phenols 9 are useful synthetic vehicles for direct applications to many other important transformations, examples of which include harnessing aryne chemistry, 23 Au-catalyzed oxidative cross-coupling, 4d,e synthesis of dibenzosiloles, 24 and catalytic synthesis of a chiral BINOL 25 scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…All hexT conjugates were characterized; if necessary, purified to ensure fidelity; recorded by DNA ligation; and diversified by amide coupling to yield a 14.496-membered tiDEL (oligothymidine-initiated DNA-encoded library) for drug screening. Our TiDEC strategy holds promise to make several catalytic strategies 11,12 available for DNA-recorded libraries, and thereby expand their chemical space. It is likely compatible with other DEL formats that are successfully used in drug research, too.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Prolific sources of drug-like structures are Brønsted acid-, and coinage metal-catalyzed reactions. 11,12 Yet, they cause depurination, 13,14 and thus require the chemically much more stable PNA for encoding. 1c,15 …”
Section: Introductionmentioning
confidence: 99%
“…These pioneering studies showed how powerful could be the use of BA catalysis for asymmetric synthesis. BINOL-derived catalysts are designed in order to get an environment both sterically demanding and moderately acid, in order to achieve good enantioselectivity and to protonate the imine nitrogen [72]. While the first studies do not elucidate the specific mechanistic pathway (even though they suggest the protonation of the imide by the phosphoric acidic site), later on, the BA catalytic activity came up.…”
Section: Brønsted Acid Catalysismentioning
confidence: 99%